Mediaeval Ismaili history and thought (Cambridge University Press, 1996)
Until recently, the Ismai`ilis were judged almost exclusively on the basis of hostile Muslim and European sources. This volume, the result of some of the most recent scholarship in the area and written by leading contemporary authorities in the field, sheds a new and more realistic light on their history